Introduction to Matrices
YouTube lecture recording from October 2020
The following YouTube video was recorded for the 2020 iteration of the course.
The material is still very similar:
Simultaneous equations
Consider 2 simultaneous equations:
a 1 x + b 1 y = c 1 , ( 1 ) a 2 x + b 2 y = c 2 , ( 2 ) \begin{align*}
a_1x+b_1y &= c_1, \qquad \qquad (1)\\
a_2x+b_2y &= c_2, \qquad \qquad (2)
\end{align*} a 1 x + b 1 y a 2 x + b 2 y = c 1 , ( 1 ) = c 2 , ( 2 )
where the values x \;x\; x and y \;y\; y are to be found, and a 1 , b 1 , a 2 , b 2 , c 1 \;a_1, \;b_1, \;a_2, \;b_2, \;c_1\; a 1 , b 1 , a 2 , b 2 , c 1 and c 2 \;c_2\; c 2 are given constants.
( 1 ) × b 2 : b 2 a 1 x + b 2 b 1 y = b 2 c 1 , ( 3 ) ( 2 ) × b 1 : b 1 a 2 x + b 1 b 2 y = b 1 c 2 , ( 4 ) ( 3 ) − ( 4 ) : b 2 a 1 x − b 1 a 2 x = b 2 c 1 − b 1 c 2 . \begin{align*}
(1) \times b_2:~~~~~~~~~~~~~~~ b_2a_1x+b_2b_1y &= b_2c_1, \qquad \qquad (3)\\
(2) \times b_1:~~~~~~~~~~~~~~~ b_1a_2x+b_1b_2y &= b_1c_2, \qquad \qquad (4)\\
(3) - (4):~~~~~~~~~~~~~~~ b_2a_1x-b_1a_2x &= b_2c_1-b_1c_2.
\end{align*} ( 1 ) × b 2 : b 2 a 1 x + b 2 b 1 y ( 2 ) × b 1 : b 1 a 2 x + b 1 b 2 y ( 3 ) − ( 4 ) : b 2 a 1 x − b 1 a 2 x = b 2 c 1 , ( 3 ) = b 1 c 2 , ( 4 ) = b 2 c 1 − b 1 c 2 .
x = b 2 c 1 − b 1 c 2 b 2 a 1 − b 1 a 2 , \displaystyle x=\frac{b_2c_1-b_1c_2}{b_2a_1-b_1a_2}, x = b 2 a 1 − b 1 a 2 b 2 c 1 − b 1 c 2 ,
y = a 1 c 2 − a 2 c 1 a 1 b 2 − a 2 b 1 . \displaystyle y=\frac{a_1c_2-a_2c_1}{a_1b_2-a_2b_1}. y = a 1 b 2 − a 2 b 1 a 1 c 2 − a 2 c 1 .
This works, provided that a 1 b 2 − a 2 b 1 ≠ 0. a_1b_2-a_2b_1\neq 0. a 1 b 2 − a 2 b 1 = 0.
While the algebraic manipulation is straightforward when solving two equations, it can get really messy when solving large systems.
What we want is a way to be able to easily manipulate linear systems, regardless of how big they are.
The matrix
Matrices are a structure that allow us to more easily manipulate linear systems.
Consider the original system
a 1 x + b 1 y = c 1 , a 2 x + b 2 y = c 2 . \begin{align*}
a_1x+b_1y &= c_1, \\
a_2x+b_2y &= c_2.
\end{align*} a 1 x + b 1 y a 2 x + b 2 y = c 1 , = c 2 .
We rewrite this, in the form of a matrix as:
( a 1 b 1 a 2 b 2 ) ( x y ) = ( c 1 c 2 ) . \begin{equation*}
\left(\begin{matrix}a_1&b_1\\ a_2&b_2\end{matrix}\right)
\left(\begin{matrix}x\\y\end{matrix}\right)
=\left(\begin{matrix}c_1\\ c_2 \end{matrix}\right).
\end{equation*} ( a 1 a 2 b 1 b 2 ) ( x y ) = ( c 1 c 2 ) .
Think about how this form relates to the original linear system.
What is a matrix?
A matrix is an array of numbers such as:
( a b c d e f g h i ) \left(\begin{matrix}a&b&c\\ d&e&f\\ g&h&i\end{matrix}\right) a d g b e h c f i
3 × 3 3\times3 3 × 3 is the size of the matrix.
A 3 × 3 3\times3 3 × 3 matrix is said to be square and have order (dimension) 3.
Addition, subtraction, and scalar multiplication
We can add or subtract two matrices as long as they have the same size:
( 2 1 3 − 4 ) + ( 6 − 5 1 − 7 ) = ( 8 − 4 4 − 11 ) \left(\begin{matrix} 2&1 \\ 3&-4 \end{matrix}\right) +\left(\begin{matrix} 6&-5 \\ 1&-7 \end{matrix}\right)= \left(\begin{matrix} 8&-4 \\ 4&-11\end{matrix}\right) ( 2 3 1 − 4 ) + ( 6 1 − 5 − 7 ) = ( 8 4 − 4 − 11 )
We can multiply a matrix by a scalar, by multiplying every element:
5 × ( 2 1 3 − 4 ) = ( 10 5 15 − 20 ) 5\times\left(\begin{matrix} 2&1\\ 3&-4 \end{matrix}\right)=\left(\begin{matrix}10&5\\ 15&-20\end{matrix}\right) 5 × ( 2 3 1 − 4 ) = ( 10 15 5 − 20 )
Matrix multiplication
To multiply two matrices, we multiply each row in the first matrix by each column in the second one, and put the results into a new matrix.
A row and column are multiplied by summing up each element in the row, multiplied by the corresponding element in the column.
( 1 2 3 4 ) ( 5 6 7 8 ) = ( 1 × 5 + 2 × 7 1 × 6 + 2 × 8 3 × 5 + 4 × 7 3 × 6 + 4 × 8 ) = ( 19 22 43 46 ) \left(\begin{matrix} 1&2 \\ 3&4 \end{matrix}\right) \left(\begin{matrix} 5&6\\7&8\end{matrix}\right) = \left(\begin{matrix} 1 \times 5 + 2 \times 7 & 1 \times 6 + 2 \times 8 \\ 3 \times 5 + 4 \times 7 & 3 \times 6 + 4\times 8\end{matrix}\right) = \left(\begin{matrix} 19&22\\43&46\end{matrix}\right) ( 1 3 2 4 ) ( 5 7 6 8 ) = ( 1 × 5 + 2 × 7 3 × 5 + 4 × 7 1 × 6 + 2 × 8 3 × 6 + 4 × 8 ) = ( 19 43 22 46 )
( 1 2 3 4 5 6 7 8 ) ( 1 2 3 4 5 6 7 8 9 10 11 12 ) = ( 70 80 90 158 184 210 ) \left(\begin{matrix} 1&2&3&4\\ 5&6&7&8 \end{matrix}\right) \left(\begin{matrix} 1&2&3\\ 4&5&6\\ 7&8&9\\ 10&11&12 \end{matrix}\right) = \left(\begin{matrix} 70&80&90\\ 158&184&210 \end{matrix}\right) ( 1 5 2 6 3 7 4 8 ) 1 4 7 10 2 5 8 11 3 6 9 12 = ( 70 158 80 184 90 210 )
( a b c ) ( p q r s v w ) = ( a p + b r + c v a q + b s + c w ) . \left(\begin{matrix} a & b & c \end{matrix}\right)
\left(\begin{matrix} p & q \\ r & s \\ v & w \end{matrix}\right)
= \left(\begin{matrix} ap+br+cv & aq+bs+cw \end{matrix}\right). ( a b c ) p r v q s w = ( a p + b r + c v a q + b s + c w ) .
If the number of columns in the first matrix doesn't match the number of rows in the second, they cannot be multiplied.
( 2 3 1 2 − 1 3 ) ( 1 0 − 1 − 4 ) = ? ? ? \left(\begin{matrix} 2 & 3 & 1 \\ 2 & -1 & 3\end{matrix}\right)\left(\begin{matrix} 1 & 0 \\ -1 & -4\end{matrix}\right) =\;?\;?\;? ( 2 2 3 − 1 1 3 ) ( 1 − 1 0 − 4 ) = ? ? ?
Matrix multiplication is not commutative
This means that A × B A \times B A × B is not the same as B × A B \times A B × A .
This can be easily seen from the fact that multiplying different sized matrices doesn't always work:
( 3 x 2 m a t r i x ) × ( 2 x 2 m a t r i x ) = ( 3 x 2 m a t r i x ) (3 x 2 \rm{matrix}) \times (2 x 2 \rm{matrix}) = (3 x 2 \rm{matrix}) ( 3 x 2 matrix ) × ( 2x2 matrix ) = ( 3x2 matrix ) > ( 2 x 2 m a t r i x ) × ( 3 x 2 m a t r i x ) = ? ? ? (2 x 2 \rm{matrix}) \times (3 x 2 \rm{matrix}) = ??? ( 2 x 2 matrix ) × ( 3x2 matrix ) = ???
However, even when sizes match, the product is usually not the same.
The identity matrix
I I I is the identity matrix, which has the property that:
A I = I A = A A I = I A = A A I = I A = A
for a square matrix A A A . It is the matrix equivalent of multiplying by 1.
The 2x2 identity matrix is:
I 2 = ( 1 0 0 1 ) . I_2 = \left(\begin{matrix} 1 & 0 \\ 0 & 1 \end{matrix}\right). I 2 = ( 1 0 0 1 ) .
The 3x3 identity matrix is:
I 3 = ( 1 0 0 0 1 0 0 0 1 ) . I_3 = \left(\begin{matrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{matrix}\right). I 3 = 1 0 0 0 1 0 0 0 1 .
and so on for higher dimensions.
Inverting matrices
The determinant
A = ( p q r s ) \displaystyle A = \left(\begin{matrix} p & q \\ r & s\end{matrix}\right) A = ( p r q s )
then the determinant of A is:
∣ A ∣ = p s − q r |A| = ps-qr ∣ A ∣ = p s − q r
That is, (top left × \times × bottom right) - (top right × \times × bottom left).
If ∣ A ∣ = 0 |A| = 0 ∣ A ∣ = 0 , A is said to be singular (and it has no inverse).
Inverting 2x2 matrices
If A B = I AB = I A B = I , what is B?
A is called the inverse of B, and vice versa. I.e.
A = B − 1 , B = A − 1 \displaystyle A = B^{-1}, B = A^{-1} A = B − 1 , B = A − 1 .
A = ( p q r s ) \displaystyle A = \left(\begin{matrix} p & q \\ r & s\end{matrix}\right) A = ( p r q s )
A − 1 = 1 p s − q r ( s − q − r p ) \displaystyle A^{-1} = \frac{1}{ps-qr} \left(\begin{matrix} s & -q \\ -r & p\end{matrix}\right) A − 1 = p s − q r 1 ( s − r − q p ) .
Example of inverting a 2x2 matrix
Let us take a matrix A = ( 2 − 3 − 2 4 ) . \displaystyle A=\left(\begin{matrix}2&-3\\ -2&4\end{matrix}\right). A = ( 2 − 2 − 3 4 ) .
First, calculate its determinant:
∣ A ∣ = ( 2 × 4 ) − ( − 3 × − 2 ) = 8 − 6 = 2. \displaystyle |A|=(2\times 4)-(-3\times-2)=8-6=2. ∣ A ∣ = ( 2 × 4 ) − ( − 3 × − 2 ) = 8 − 6 = 2.
A − 1 = 1 2 ( 4 3 2 2 ) \displaystyle A^{-1}={1\over 2}\left(\begin{matrix}4&3\\ 2&2\end{matrix}\right) A − 1 = 2 1 ( 4 2 3 2 )
As a check, calculate A − 1 A A^{-1}A A − 1 A :
A − 1 A = 1 2 ( 4 3 2 2 ) ( 2 − 3 − 2 4 ) \displaystyle A^{-1}A= \frac{1}{2}\left(\begin{matrix}4&3\\ 2&2\end{matrix}\right)\left(\begin{matrix}2&-3\\ -2&4\end{matrix}\right) A − 1 A = 2 1 ( 4 2 3 2 ) ( 2 − 2 − 3 4 )
= 1 2 ( 2 0 0 2 ) \displaystyle = \frac{1}{2}\left(\begin{matrix}2&0\\ 0&2\end{matrix}\right) = 2 1 ( 2 0 0 2 )
= ( 1 0 0 1 ) \displaystyle = \left(\begin{matrix}1&0\\ 0&1\end{matrix}\right) = ( 1 0 0 1 )
= I 2 . \displaystyle =I_2. = I 2 .
The transpose of a Matrix
A T A^T A T is the transpose of A A A .
Swap elements across the leading diagonal so that A i j T = A j i A^T_{ij}= A_{ji} A ij T = A ji .
A = ( 2 1 2 1 4 6 1 − 1 2 ) \displaystyle A=\left(\begin{matrix}2&1&2\\ 1&4&6\\ 1&-1&2\end{matrix}\right) A = 2 1 1 1 4 − 1 2 6 2 > A T = ( 2 1 1 1 4 − 1 2 6 2 ) \displaystyle A^T=\left(\begin{matrix}2&1&1\\ 1&4&-1\\ 2&6&2\end{matrix}\right) A T = 2 1 2 1 4 6 1 − 1 2
Solving a linear system using matrices
To solve a matrix system A x = b \displaystyle A {\bf x} = {\bf b} A x = b for an unknown left-hand side x {\bf x} x .
If it's of order 2 then use the formula to write A − 1 A^{-1} A − 1 and hence x = A − 1 b {\bf x} = A^{-1}{\bf b} x = A − 1 b .
If it's larger ( 3 × 3 ) (3\times3) ( 3 × 3 ) then there's still a formula for A − 1 A^{-1} A − 1 (not in this course).
Use an analytical method (Gaussian elimination) to find the inverse (not in this course).
Use a numerical scheme to find an approximation to x {\bf x} x , such as Newton's method (not in this course).
Solve using linear algebra software (e.g. in Python, which we will see shortly).
Example of solving a 2x2 linear system
A − 1 A x = A − 1 b \displaystyle A^{-1}A{\bf x}=A^{-1}{\bf b} A − 1 A x = A − 1 b
x = A − 1 b \displaystyle {\bf x}=A^{-1}{\bf b} x = A − 1 b
x + 5 y = 11 , − x + 5 y = 9 \begin{align*}
x+5y &= 11, \\
-x+5y &= 9
\end{align*} x + 5 y − x + 5 y = 11 , = 9
In matrix form, this gives:
( 1 5 − 1 5 ) ( x y ) = ( 11 9 ) \displaystyle \left(\begin{matrix}1 &5\\ -1&5\end{matrix}\right) \left(\begin{matrix}x\\ y\end{matrix}\right) = \left(\begin{matrix}11\\ 9\end{matrix}\right) ( 1 − 1 5 5 ) ( x y ) = ( 11 9 )
A − 1 = 1 10 ( 5 − 5 1 1 ) \displaystyle A^{-1}= \frac{1}{10} \left(\begin{matrix}5 &-5\\ 1&1 \end{matrix}\right) A − 1 = 10 1 ( 5 1 − 5 1 )
( x y ) = 1 10 ( 5 − 5 1 1 ) ( 11 9 ) = 1 10 ( 10 20 ) \displaystyle \left(\begin{matrix}x\\ y\end{matrix}\right) = \frac{1}{10}\left(\begin{matrix}5 &-5\\ 1&1\end{matrix}\right)\left(\begin{matrix}11\\ 9\end{matrix}\right) =\frac{1}{10} \left(\begin{matrix}10\\ 20\end{matrix}\right) ( x y ) = 10 1 ( 5 1 − 5 1 ) ( 11 9 ) = 10 1 ( 10 20 ) > = ( 1 2 ) \displaystyle =\left(\begin{matrix}1\\ 2\end{matrix}\right) = ( 1 2 )
And x = 1 , y = 2 x=1, y=2 x = 1 , y = 2
This process seems like more effort than its worth for small systems.
But it allows for a much more systematic approach when dealing with large systems.
As the size of the matrix grows, this process can be easily performed with Python (or other tools).
Example. Solving a 4x4 system in Python
x + 5 y + 3 z − w = 5 , x − 2 y + z + 4 w = 2 , − 3 x + y − z + 2 w = − 5 , x + y + z = 0. \begin{align*}
x + 5y + 3z - w &= 5, \\
x - 2y + z + 4w &= 2, \\
-3x + y - z + 2w &= -5, \\
x + y + z &= 0.
\end{align*} x + 5 y + 3 z − w x − 2 y + z + 4 w − 3 x + y − z + 2 w x + y + z = 5 , = 2 , = − 5 , = 0.
In matrix form, this gives:
( 1 5 3 − 1 1 − 2 1 4 − 3 1 − 1 2 1 1 1 0 ) ( x y z w ) = ( 5 2 − 5 0 ) . \displaystyle \left(\begin{matrix} 1 & 5 & 3 & -1 \\ 1 & -2 & 1 & 4 \\ -3 & 1 & -1 & 2\\ 1 & 1 & 1 & 0 \end{matrix}\right) \left(\begin{matrix} x \\ y \\ z \\ w\end{matrix}\right) = \left(\begin{matrix} 5 \\ 2 \\ -5 \\ 0\end{matrix}\right). 1 1 − 3 1 5 − 2 1 1 3 1 − 1 1 − 1 4 2 0 x y z w = 5 2 − 5 0 .
Numerically, using NumPy
Copy # In python, we use numpy arrays to store the needed matrices
# the procedure linalg.solve, solves the system Ax = b
# We could also calculate the inverse of A (linalg.inv), and then multiply.
# But this is faster
import numpy as np
A = np . array ( [ [ 1 , 5 , 3 , - 1 ] , [ 1 , - 2 , 1 , 4 ] , [ - 3 , 1 , - 1 , 2 ] , [ 1 , 1 , 1 , 0 ] ] )
b = np . array ( [ 5 , 2 , - 5 , 0 ] )
x = np . linalg . solve ( A , b )
print ( x )
print ( np . matmul ( A , x ) )
Copy [-5.94444444 -5.11111111 11.05555556 -3.33333333]
[ 5.0000000e+00 2.0000000e+00 -5.0000000e+00 -8.8817842e-16]
Symbolically, using SymPy
Copy import sympy as sp
A = sp . Matrix ( [ [ 1 , 5 , 3 , - 1 ] , [ 1 , - 2 , 1 , 4 ] , [ - 3 , 1 , - 1 , 2 ] , [ 1 , 1 , 1 , 0 ] ] )
A . inv ( ) * sp . Matrix ( [ 5 , 2 , - 5 , 0 ] )
[ − 107 18 − 46 9 199 18 − 10 3 ] \displaystyle \left[\begin{matrix}- \frac{107}{18}\\- \frac{46}{9}\\\frac{199}{18}\\- \frac{10}{3}\end{matrix}\right] − 18 107 − 9 46 18 199 − 3 10
Introductory problems
Introductory problems 1 Write the following system of equations:
x + y + z = 7 2 x − y + z = 2 x − 2 y + 2 z = 5 \begin{aligned}
x + y + z &= 7\\
2x - y + z &= 2\\
x - 2y + 2z &= 5
\end{aligned} x + y + z 2 x − y + z x − 2 y + 2 z = 7 = 2 = 5
A x = b \displaystyle A\mathbf{x} = \mathbf{b} A x = b
y B = c \displaystyle \mathbf{y}B = \mathbf{c} y B = c
Where A A A and B B B are 3 × 3 3\times3 3 × 3 matrices, and x \mathbf{x} x , y \mathbf{y} y , b \mathbf{b} b and c \mathbf{c} c are vectors whose size and shape you should carefully indicate.
Check that your answers make sense by expanding your expressions to ensure you get back to the original equations.
Introductory problems 2
A = ( 2 1 3 4 ) \displaystyle A = \begin{pmatrix} 2 & 1 \\ 3 & 4 \end{pmatrix} A = ( 2 3 1 4 )
B = ( 1 4 7 2 ) \displaystyle B = \begin{pmatrix} 1 & 4 \\ 7 & 2 \end{pmatrix} B = ( 1 7 4 2 )
C = ( 3 − 1 − 5 2 ) \displaystyle C = \begin{pmatrix} 3 & -1 \\ -5 & 2 \end{pmatrix} C = ( 3 − 5 − 1 2 )
D = ( 1 3 ) \displaystyle D = \begin{pmatrix} 1 \\ 3 \end{pmatrix} D = ( 1 3 )
E = ( 2 − 1 ) \displaystyle E = \begin{pmatrix} 2 & -1 \end{pmatrix} E = ( 2 − 1 )
Write down a 21 a_{21} a 21 , b 12 b_{12} b 12 and c 22 c_{22} c 22
Calculate, where possible, or explain why the product is not defined:
Do A and B commute? Do A and C commute?
Does ( A B ) C = A ( B C ) (AB)C = A(BC) ( A B ) C = A ( BC ) ? Does this either prove or disprove that matrix multiplication is associative?
Does A C + B C = ( A + B ) C AC + BC = (A+B)C A C + BC = ( A + B ) C ? Does this either prove or disprove the distributive property of matrices?
Main problems
Main problems 1 If A = 1 2 ( 1 1 1 1 ) \displaystyle A = \frac{1}{2}\left(\begin{array}{cc} 1 & 1 \\ 1 & 1 \end{array}\right) A = 2 1 ( 1 1 1 1 ) , find A 2 A^2 A 2 and A 3 A^3 A 3 and comment on your results.
Main problems 2
A = ( 2 1 3 3 − 2 1 − 1 0 1 ) ; B = ( 0 − 1 1 − 5 2 − 1 3 0 2 ) \displaystyle A = \begin{pmatrix} 2 & 1 & 3 \\ 3 & -2 & 1 \\ -1 & 0 & 1 \end{pmatrix}; \qquad B = \begin{pmatrix} 0 & -1 & 1 \\ -5 & 2 & -1 \\ 3 & 0 & 2 \end{pmatrix} A = 2 3 − 1 1 − 2 0 3 1 1 ; B = 0 − 5 3 − 1 2 0 1 − 1 2
Main problems 3 Find the determinant, ∣ A ∣ |A| ∣ A ∣ , of the following matrices:
A = ( 1 2 1 6 ) \displaystyle A = \begin{pmatrix} 1 & 2 \\ 1 & 6 \end{pmatrix} A = ( 1 1 2 6 )
A = ( 1 − 1 2 − 4 ) \displaystyle A = \begin{pmatrix} 1 &-1 \\ 2 &-4 \end{pmatrix} A = ( 1 2 − 1 − 4 )
Main problems 4 Find the inverse, A − 1 A^{-1} A − 1 , of the following matrices:
A = ( 2 5 − 1 4 ) A = \begin{pmatrix} 2 & 5 \\-1 & 4 \end{pmatrix} A = ( 2 − 1 5 4 )
A = ( − 3 2 − 1 7 ) A = \begin{pmatrix} -3 & 2 \\-1 & 7 \end{pmatrix} A = ( − 3 − 1 2 7 )
Main problems 5 Use Python's numpy.linalg.solve
to solve the following systems of equations:
x + 2 y − 3 z = 9 , 2 x − y + z = 0 , 4 x − y + z = 4. \begin{aligned} x + 2y - 3z &= 9,\\ 2x - y + z &= 0,\\ 4x - y + z &= 4. \end{aligned} x + 2 y − 3 z 2 x − y + z 4 x − y + z = 9 , = 0 , = 4.
x + 5 y + 3 z = 17 , 5 x + y − 2 z = 4 , x + 2 y + z = 7. \begin{aligned}x + 5y + 3z &= 17,\\ 5x + y - 2z &= 4,\\ x + 2y + z &= 7. \end{aligned} x + 5 y + 3 z 5 x + y − 2 z x + 2 y + z = 17 , = 4 , = 7.
2 y + z = − 8 , x − 2 y − 3 z = 0 , − x + y + 2 z = 3. \begin{aligned} 2y + z &= -8,\\ x - 2y - 3z &= 0,\\ -x + y + 2z &= 3. \end{aligned} 2 y + z x − 2 y − 3 z − x + y + 2 z = − 8 , = 0 , = 3.
Copy # hint
import numpy as np
A = np . array ( [ [ 1 , 2 , - 3 ] , [ 2 , - 1 , 1 ] , [ 4 , - 1 , 1 ] ] )
b = np . array ( [ 9 , 0 , 4 ] )
x = np . linalg . solve ( A , b )
print ( x )
Main problems 6
X = ( 1 2 3 4 ) ; Y = ( 5 6 7 8 ) \displaystyle X = \begin{pmatrix} 1 & 2 \\ 3 & 4 \end{pmatrix}; \qquad Y = \begin{pmatrix} 5 & 6 \\ 7 & 8 \end{pmatrix} X = ( 1 3 2 4 ) ; Y = ( 5 7 6 8 )
Extension problems
Extension problems 1
( 3 1 1 3 ) ( 1 2 1 2 ) = λ 1 ( 1 2 1 2 ) \begin{pmatrix} 3 & 1 \\ 1 & 3 \end{pmatrix} \begin{pmatrix} \frac{1}{\sqrt 2} \\ \frac{1}{\sqrt 2} \end{pmatrix} = \lambda_1 \begin{pmatrix} \frac{1}{\sqrt 2} \\ \frac{1}{\sqrt 2} \end{pmatrix} ( 3 1 1 3 ) ( 2 1 2 1 ) = λ 1 ( 2 1 2 1 ) > ( 3 1 1 3 ) ( 1 2 − 1 2 ) = λ 2 ( 1 2 − 1 2 ) \begin{pmatrix} 3 & 1 \\ 1 & 3 \end{pmatrix} \begin{pmatrix} \frac{1}{\sqrt 2} \\ \frac{-1}{\sqrt 2} \end{pmatrix} = \lambda_2 \begin{pmatrix} \frac{1}{\sqrt 2} \\ \frac{-1}{\sqrt 2} \end{pmatrix} ( 3 1 1 3 ) ( 2 1 2 − 1 ) = λ 2 ( 2 1 2 − 1 )
where λ 1 \lambda_1 λ 1 and λ 2 \lambda_2 λ 2 are constants to be determined.